Performance analysis of regional finance management in musirawas regency office indonesia - Yohanes Susanto; Gunadi (Program Studi S3 Ilmu Manajemen, 2022)
This study aimed to find out the relationship and influence of competency, commitment, and work motivation on regional finance management in Department of Planning and Finance in Musirawas Regency Office. This study was carried out on 40 employees in Department of Planning and Finance in Musirawas Regency Office. Data were collected by survey method through distributing questionnaires and then processed by SPSS 24 program. This study used ex post facto descriptive analysis. Based on the results, the three variables namely competency, commitment and motivation had a significant and positive influence on performance in the Department of Planning and Finance in Musirawas Regency Office partially and simultaneously. This shows that employees placed in regional financial management are required to have competency, knowledge, skills and understanding in the field of financial accounting.